Immune Defect in Adults With Down Syndrome: Insights Into a Complex Issue - Dieudonné, Yannick; Uring-Lambert, Beatrice; Jeljeli, Mohamed Maxime; Gies, Vincent; Alembik, Yves; Korganow, Anne-Sophie; Guffroy, Aurélien (Frontiers in Immunology, 2020)
Children with Down syndrome (DS) suffer from recurrent respiratory infections, which represent the leading cause of mortality during childhood. This susceptibility to infections is usually considered multifactorial and related to both impaired immune function and non-immunological factors. Infections are also one of the top causes of death in DS at adulthood. DS is considered an immunodeficiency with syndromic features by some researchers because of this high rate of infection and the immunological characteristics observed in children with DS. Little is known about the immune status of adult patients. Herein, we report the clinical and immune phenotype of 44 adults with DS, correlated with their infectious history. We observed that these adults had an aberrant lymphocyte phenotype with decreased naïve/memory T cell ratios and reduced numbers of switched memory B cells. The lower incidence of infectious events at adulthood distinguish DS from other inborn errors of immunity. Primary immunodeficiency-related features in DS could explain the increased risk of developing autoimmunity, malignancies, and infections. During adulthood, this immune dysfunction may be compensated for in mid-life, and infection-related mortality observed in older patients might be favored by multiple factors such as neurological impairment or nosocomial antigen exposure.